Understanding Translanguaging in Bebandem Vocational High School EFL Classroom: Strategies and Teacher Pedagogical Reasoning - Ida Bagus Diagung Putradi Widh Swandha; Made Hery Santosa; I Ketut Trika Adi Ana (CV. Ulil Albab Corp, 2026)
This study explores translanguaging in a vocational high school English classroom at the Bebandem district, in Bali, focusing on the teacher’s translanguaging strategy and the reasons behind its use. The study was conducted in a 10th-grade English class of the Hotel Hospitality program, a multilingual classroom setting where students and teachers regularly use English, Bahasa Indonesia, and Basa Bali. With basic qualitative study design, data were collected through classroom observations and a semi-structured teacher interview. The results revealed twelve translanguaging strategies used by the teacher, which were then inductively organized into three functional themes, which cover facilitating comprehension and instruction, promoting peer interaction and collaboration, and supporting students’ language output. The interview results further indicated that the teacher’s use of translanguaging was guided by pedagogical considerations related to students’ language proficiency, learning challenges, and classroom dynamics in EFL multilingual settings. Time triangulation across data suggested that translanguaging in this vocational EFL context functioned as an intentional instructional strategy rather than merely spontaneous language alternation. This study contributes to translanguaging research by highlighting how translanguaging was used as pedagogically focused functions in vocational EFL classrooms, emphasizing the role of teacher awareness in building effective instruction in multilingual settings.